Seed oil physicochemical characterization from non-edible Pancratium maritimum - Jouaidi Marwa; Rahmani Rami; Mohamed Debouba (Journal of Oasis Agriculture and Sustainable Development)
The oil extracted from Pancratium maritimum seeds was subjected to qualitative (acidity, K232, K270, chlorophyll content) and quantitative (polyphenol content, fatty acid composition) characterization. The P. maritimum seed oil showed an acidity of 0.22 mg/g, a k232 extinction coefficients of 2.6% and total polyphenol contents of 89.5 mg EGA/Kg. The chlorophyll contents were similar to that commonly recorded for edible vegetable oils. Interestingly, the P. maritimum seed oil was enriched in fatty acids distributed into 11 fatty acids with the most abundant fatty acids being the linoleic acid (41.1%), oleic acid (39.9%) and palmitic acid (14.95%). Taken together, P. maritimum oil contains antioxidant compounds (chlorophyll and polyphenols) and fatty acid composition potentially useful for pharmaceutical and cosmetic application.